A cost-benefit analysis of livelihood, environmental and health benefits of a large scale water filter and cookstove distribution in Rwanda - Christina Barstow; Randall Ames Bluffstone; Kyle Silon; Karl Linden; Evan Thomas (Development Engineering, 2019)
Public health interventions targeting contaminated drinking water and indoor air pollution may help to reduce two of the leading causes of death among children under 5 in Rwanda - diarrhea and pneumonia. These interventions also have the potential to provide economic benefits, including reduction in expenditures on fuelwood and time spent on fuelwood collection, environmental benefits through reductions in deforestation and greenhouse gas emissions, and additional economic benefits attributable to health impacts. We evaluate one such large scale intervention, the Tubeho Neza program in Western Rwanda using a cost-benefit analysis. This paper estimates monetized program benefits related to fuelwood savings, time savings, environmental and health benefits, which are then compared to the overall program cost, over a 5 year project year period. The total program cost is estimated at over 11.91 million, and total benefits at the means valued at over 66.67 million, for an estimated mean cost-benefit ratio of over 5.6. A sensitivity analysis of the major factors indicated a cost-benefit ratio range of approximately 1-16. The primary benefit identified is the environmental impact of woodfuel savings attributable to the improved cookstoves. This study estimates 118,000 tonnes of annual woodfuel savings in the Western Province may be attributable to the program in year 1, decreasing to 65,000 tonnes in year 5. These estimates suggest that this program may help to compensate for the government of Rwanda's projected regional woodfuel deficit of 106,000 tonnes per year by 2020. Overall, this study suggests that the Tubeho Neza program provides benefits in excess of the program costs.
Keywords: 330; Cost benefit analysis; Water filters; Cookstoves; Public health; Deforestation